eCM 2013
DOI: 10.22203/ecm.v025a02
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorodecalin and bone regeneration

Abstract: Perfluorodecalin (PFD) is a chemically and biologically inert biomaterial and, as many perfluorocarbons, is also hydrophobic, radiopaque and has a high solute capacity for gases such as oxygen. In this article we have demonstrated, both in vitro and in vivo, that PFD may significantly enhance bone regeneration. Firstly, the potential benefit of PFD was demonstrated by prolonging the survival of bone marrow cells cultured in anaerobic conditions. These findings translated in vivo, where PFD incorporated into bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Intraosseous defect models are necessary to assess the possibility of clinical application for orthopaedic and craniofacial surgery. To evaluate biocompatibility, biodegradation and vascularisation, subcutaneous or intramuscular implantation models in mouse or rat are recommended [22,42,69,46,73,82,[84][85][86]88,90,93,94,96,[100][101][102][103]. But these models may not be suitable to answer questions of osteoinduction of granular bone grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraosseous defect models are necessary to assess the possibility of clinical application for orthopaedic and craniofacial surgery. To evaluate biocompatibility, biodegradation and vascularisation, subcutaneous or intramuscular implantation models in mouse or rat are recommended [22,42,69,46,73,82,[84][85][86]88,90,93,94,96,[100][101][102][103]. But these models may not be suitable to answer questions of osteoinduction of granular bone grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Using light microscopy slides have to be stained to evaluate presence of bone. Regular histopathological staining for bone are van Kossa, alcain blue or alkaline Phosphatase, whereas the last is usually stained within the cells themselves and not within the extracellular matrix [22][23][24][25][26][27][28][29][30][31][32]60,[67][68][69]71,73,75,[90][91][92][93][94][95][96][97][98][99][100][101][102]105,109,[116][117][118][119][120][121]. When applying the scanning microscopy, tissue is characterised morphologically, transmission electron microscopy allows for ultrastructural morphological evaluation [22,60,75,90,105,[116][117][118][119]…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous GelMA solution and fluorinated perfluorodecalin oil (Synquest Laboratories, Alachua, Florida) were selected as the dispersion and continuous phases, respectively. 22,23 A CorSolutions PneuWave dual channel pump (CorSolutions, Ithaca, New York), with a flow rate range of 0-120 lL/min for pressures from 0 to 14.5 psi, respectively, was used for this work. The pump was connected to the microfluidic device using FEP microtubing (ID: 0.0200; INDEX Health & Science Inc LLC, Oak Harbor, Washington) capped with 23G-1 needles.…”
Section: Generation Of Gelma Microspheresmentioning
confidence: 99%
“…Habibovic et al tested 3D-printed brushite-based scaffolds on the decorticated lumbar transverse processes of goats for 3 months, 10 while Tamimi et al tested implants with a similar composition in a calvarial bone surface of rabbits. 17 Although promising, translational animal studies of biomaterial performance for intended human application should ideally be performed in large animal species, as small laboratory animals possess superior regenerative ability compared to humans and larger animals. 18 Also, in vivo studies should be of sufficient duration to allow assessment of long-term effects and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that three-dimensional powder printing (3DPP) is a promising manufacturing technique for the fabrication of individual ceramic-based bone grafts. In previous works, we have used a low-temperature processing regime to produce personalized ceramic matrices composed of TCP and/or brushite mineral phases. , The suitability of these materials for bone replacement has been confirmed by few in vivo implantation experiments. Habibovic et al tested 3D-printed brushite-based scaffolds on the decorticated lumbar transverse processes of goats for 3 months, while Tamimi et al tested implants with a similar composition in a calvarial bone surface of rabbits . Although promising, translational animal studies of biomaterial performance for intended human application should ideally be performed in large animal species, as small laboratory animals possess superior regenerative ability compared to humans and larger animals .…”
Section: Introductionmentioning
confidence: 99%